Molah Gati Innovation in Improving The Quality And Efficiency of School Administration in Mataram City - Uchaimid Biridlo'i Robby; Tania Andari; Adi Suhendra; Soeharto Soeharto (STKIP Singkawang, 2024)
Education as a sector that also experiences significant impacts from technological developments requires innovation in overcoming the complex challenges of school administration. This research article discusses the implementation of Integrated Digital-Based School Management, or Molah Gati, in Mataram City. This initiative is in line with the global movement towards digital transformation in education. Molah Gati uses a Belajar.id account based on Google Workspace for Education (GWE) to integrate various digital features, such as Google Site, Google Form, Google Sheet, Google Meet, Google Drive, and Google Doc. The goal of Molah Gati implementation is to improve the efficiency and effectiveness of school administration. This article provides a concrete evaluation of the implementation of Molah Gati at SDN 23 Ampenan, Mataram City, using qualitative research methods. The results show the positive impact of Molah Gati in the efficiency of letter filing, online teacher meetings, real-time monitoring of teaching tools, extracurricular recording, and reporting of educational activities. This innovation was successfully replicated in several regions and received significant support from related parties, as indicated by the Regional Innovation Index.